Findings from the Tushirikiane mobile health (mHealth) HIV self‐testing pragmatic trial with refugee adolescents and youth living in informal settlements in Kampala, Uganda - Logie, Carmen H.; Okumu, Moses; Berry, Isha; Hakiza, Robert; Baral, Stefan D.; Musoke, Daniel Kibuuka; Nakitende, Aidah; Mwima, Simon; Kyambadde, Peter; Loutet, Miranda; Batte, Shamilah; Lester, Richard; et al. (Journal of the International AIDS Society, 2023)
IntroductionUrban refugee youth remain underserved by current HIV prevention strategies, including HIV self-testing (HIVST). Examining HIVST feasibility with refugees can inform tailored HIV testing strategies. We examined if HIVST and mobile health (mHealth) delivery approaches could increase HIV testing uptake and HIV status knowledge among refugee youth in Kampala, Uganda.MethodsWe conducted a three-arm pragmatic controlled trial across five informal settlements grouped into three sites in Kampala from 2020 to 2021 with peer-recruited refugee youth aged 16–24 years. The intervention was HIVST and HIVST + mHealth (HIVST with bidirectional SMS), compared with standard of care (SOC). Primary outcomes were self-reported HIV testing uptake and correct status knowledge verified by point-of-care testing. Some secondary outcomes included: depression, HIV-related stigma, and adolescent sexual and reproductive health (SRH) stigma at three time points (baseline [T0], 8 months [T1] and 12 months [T2]). We used generalized estimating equation regression models to estimate crude and adjusted odds ratios comparing arms over time, adjusting for age, gender and baseline imbalances. We assessed study pragmatism across PRECIS-2 dimensions.ResultsWe enrolled 450 participants (50.7% cisgender men, 48.7% cisgender women, 0.7% transgender women; mean age: 20.0, standard deviation: 2.4) across three sites. Self-reported HIV testing uptake increased significantly from T0 to T1 in intervention arms: HIVST arm: (27.6% [n = 43] at T0 vs. 91.2% [n = 135] at T1; HIVST + mHealth: 30.9% [n = 47] at T0 vs. 94.2% [n = 113] at T1]) compared with SOC (35.5% [n = 50] at T0 vs. 24.8% [ = 27] at T1) and remained significantly higher than SOC at T2 (p<0.001). HIV status knowledge in intervention arms (HIVST arm: 100% [n = 121], HIVST + mHealth arm: 97.9% [n = 95]) was significantly higher than SOC (61.5% [n = 59]) at T2. There were modest changes in secondary outcomes in intervention arms, including decreased depression alongside increased HIV-related stigma and adolescent SRH stigma. The trial employed both pragmatic (eligibility criteria, setting, organization, outcome, analysis) and explanatory approaches (recruitment path, flexibility of delivery flexibility, adherence flexibility, follow-up).ConclusionsOffering HIVST is a promising approach to increase HIV testing uptake among urban refugee youth in Kampala. We share lessons learned to inform future youth-focused HIVST trials in urban humanitarian settings.